Solid Waste Management along Lake Victoria Beeches - Obongo, Thomas; Okotto, Lorna; Kinaro, Zackary (World Environment, 2021)
The production of solid waste materials due to, Uncontrolled growth of beaches in terms of population and structures, have led to environmental and health problems in the area. Although several studies have been undertaken on waste management in general, little has been done on solid waste management in the beaches around Lake Victoria. The objective of this study was to examine the existing methods used in managing the different types of solid wastes. The study was anchored on the cost-benefit analysis theory. Descriptive cross sectional survey design has been used to collect both qualitative and quantitative data. The target population of the study area was 420 people and a sample size of 189 household representatives was selected for the study. Proportional sampling was used to determine sample size while simple random sampling was used to select individual respondents. Questionnaires, interviews, focus group discussions and observations were used to collect data. The study revealed that dumping of solid waste was the most used method of waste disposal regardless of the type of waste produced. Waste management strategy that promote use of food and other organic wastes, but also leverages on initiatives in reuse and recycling can improve waste management in the beaches.
Keywords: Integrated Solid Waste Management; Environmental Hazard; Sampling Techniques